The mechanism of pH recalibration by dissolved oxygen in alkaline modified aquaculture seawater - Anggayasti, Wresti L.; Satrio N., Willy; Wardana, I Nyoman Gede; Kurniawan, Andi (Eastern-European Journal of Enterprise Technologies, 2022)
The balance of dissolved oxygen and pH levels is paramount in aquaculture, as a media for cultivating aquatic organisms under controlled conditions. An imbalance in both oxygen and pH could severely harm the cultured aquatic organisms. Various strategies are used to prevent hypoxia and maintain the pH level of the culture. Interestingly, hypoxia or deprivation of oxygen supply in aquaculture was often reported to co-occur with the seawater acidification. Despite that, there was no evidence that the O2 level was directly linked to pH changes. Thus, the existing treatment strategies are separated between O2 and pH maintenances, which often inflate cost and cause environmental burden due to the use of synthetic chemicals. This study was conducted to observe the mechanism and effect of the O2 addition to aquaculture seawater in molecular level when the pH value of the water was modified. The understanding of the mechanism may lead to an alternative to the harmful aquaculture treatments. The molecular mechanics analysis was applied to examine the mechanism of pH adjustment in non-aerated and aerated seawater. The results indicated that O2 accelerated the pH recalibration of seawater, particularly in the alkaline modified samples compared to the acid modified samples. Mechanical simulations further showed the repulsion between and O2 causes vibration which shortens OH bond by 17.71 % while elongates O-O bond by 1.00 %. Additionally, the spin coupling between OH- and O2 promotes global energy transfer which stimulates the vibration of the alkaline modified water system. Together, those mechanisms enabled the pH value to return to the baseline. These findings contribute a molecular mechanism view of aquaculture pH maintenance in the presence of O2, as well as revisiting the use of aeration in aquaculture treatment